Biomedical Applications of Chitosan Nanoparticles: A Comprehensive Review (World Journal of Experimental Biosciences, 2019)
Chitosan nanoparticles (CSNPs) are a versatile polyfunctional mechano-chemical scaffold used to advance biomedicine through long-term retention in cells and tissues after delivery. Because CSNPs have multiple properties that facilitate drug delivery, including being biodegradable, biocompatible, cationically charged, mucoadhesive, possessing some inherent biological activity, and easily penetrating mucosal membranes, they are an important part of polymeric nanocarriers for drug delivery. This article offers a comprehensive and critical review of the physical and chemical properties of CSNPs and highlights various biomedical applications, such as serving as a delivery vehicle for medicine via (i) oral, (ii) nasal, (iii) pulmonary, (iv) ocular, (v) anticancer, (vi) gene therapy, (vii) vaccine adjuvants, (viii) tissue repair or wound healing, (ix) tissue regeneration, (x) antimicrobial activity, (xi) clinical studies against pathogens, (xii) cellular uptake and intracellular transport mechanisms, mucoadhesion, and the paradox of mucosal penetration, (xiii) development of safety and toxicology profiles from in vitro and in vivo preclinical studies, (xiv) surface modifications such as PEGylation and receptor-ligand conjugation for cell-specific targeting, and (xv) barriers to translating CSNPs from laboratory research to clinical use, along with future directions like delivering CRISPR/Cas9, developing theranostics, and microfluidic manufacturing of CSNPs. CSNPs consistently improve bioavailability, enhance cellular uptake, increase accumulation in tumors, prolong drug release, and reduce pathogen loads, often outperforming both free and conventional drugs across all delivery routes and medication types studied. Nevertheless, challenges such as manufacturing scale-up, raw material variability, limited correlation models between in vitro and in vivo data, and an evolving regulatory environment for polymeric nanomedicines impede clinical translation. This review critically discusses these obstacles and proposes strategies for the next generation of chitosan-based nanomedicine.